A Case Report: Prevost’s as Early Sign of Subcortical Symptom to be Considered or Screening in Acute Ischemic Stroke - Fitria Febriana; Andrianto Selohandono; Yudhanto Utomo (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Stroke is the leading cause of death and disability. Stroke symptoms depend on the location of the lesion, whether cortical or subcortical (white matter, basal ganglia, or thalamus). Prevost's sign or horizontal conjugate eye deviation (CED) must be considered an early motoric sign of ischemic stroke. Case: Mrs. F, 61 years old, came to the ER complaining of headache and dizziness for a day without any complaints about her eyes, and had a history of diabetes mellitus. Neurological examination revealed conjugate eye deviation to the right side without other neurological deficits. A head CT scan showed a minimal infarction of the left putamen and an old minimal infarction of the right corona radiata. Discussion: Pathophysiologic mechanism of Prevost’s sign due to cerebral-mesencephalic-phonto-cerebellar pathway disorder and related to cranial nerves III and VI. The putamen is a nuclear structure part of the basal ganglia involved in that pathway. A provost's sign that appears in less than 90 days can be used for stroke screening for ischemic patients. Previous studies describe CED >140 as being identified as ischemic stroke. Patients with strabismus have an average of CED 14.20. Another retrospective study in 543 acute ischemic strokes showed that CED had a higher specificity value (0.78; 95% CI) than hemiparesis (0.35; 95% CI). The sensitivity values were 0.76 and 0.85 (95% CI). Conclusion: Prevost's sign is one of the signs of motor deficit in acute cerebral infarction. It needs to be considered as a subcortical lesion in stroke patients.